Effects of oral, oronasal, and oronasal breathing with a decongested nose during incremental maximal exercise testing of well-trained endurance athletes: a randomized cross-over study - Bergqvist, J.; Reite, F.; Edin, F.; Schiöler, L.; Börjesson, M.; Steinsvåg, S.; Pettersson, S.; Hellgren, J. (Frontiers in Physiology, 2025)
IntroductionNasal breathing is preferable for persons at rest and remains partially active during oronasal breathing in exercise. However, its potential contribution to performance–particularly in cases with a decongested nose–remains understudied in well-trained athletes. This study investigates whether nasal airflow during oronasal breathing influences performance in well-trained, endurance athletes. Specifically, we examine whether nasal decongestion during oronasal breathing enhances ventilatory efficiency and, thereby, improves time-to-exhaustion (TTE), maximal oxygen uptake (V˙O2max), and maximum power output (Wmax), as compared to oral-only breathing.MethodsTwelve male, well-trained cyclists/triathlon athletes (mean V˙O2max, 67.2 ± 5.5 mL kg-1·min-1) with age range of 30.6 ± 8.7 years, were included. Two characterization tests were performed: 1) an incremental cycle test to determine V˙O2max and Wmax; and 2) a familiarization trial of the experimental exercise protocol. The three experimental exercise trials consisted of five 6-min submaximal steady-state levels (50 W and 100 W at 50 rpm for the first two stages, followed by 40%, 58%, and 75% of the individual Wmax at 80 rpm), concluding with a TTE test.ResultsThere were no significant differences between the three breathing modes (p > 0.05) in terms of the cardiopulmonary or performance parameters, including the rate of perceived exertion, respiratory frequency, mean minute ventilation, V˙O2max, and Wmax. Although not statistically significant (p > 0.05) TTE was 2.8% and 4.2% longer during oronasal and decongested oronasal breathing, respectively, as compared to oral-only breathing. The mean capillary blood lactate level was significantly (p < 0.05) lower immediately after and 3 min after the TTE test in the oral-only breathing condition (9.12 ± 2.20 mmol/L), as compared with the oronasal (9.83 ± 2.19 mmol/L, Cohen’s d = 0.43) and decongested-nose (9.81 ± 2.29 mmol/L, d = 0.41) conditions.ConclusionOral-only breathing is associated with a non-significant shorter TTE than oronasal breathing with or without nasal decongestion, although it results in significantly lower mean capillary blood lactate levels following maximal aerobic exercise. These findings suggest that a single, low-resistance oral breathing route reduces lactate accumulation under maximal effort, whereas oronasal breathing–particularly in the presence of nasal decongestion–may be more beneficial for sustaining endurance.